Prática de suplementação de micronutrientes em pacientes com síndrome metabólica e obesidade: análise da ingestão dietética e conduta profissional - Soyer, Aline de Brito (Universidade do Vale do Rio dos Sinos, 2025)
Metabolic Syndrome (MS) is characterized by a cluster of interrelated risk factors, including abdominal obesity, hyperglycemia, hypertension, and dyslipidemia, and is associated with an increased risk of type 2 diabetes (T2DM), cardiovascular events, and mortality. Obesity and T2DM are chronic conditions with high prevalence and significant impact on public health. Despite frequently excessive caloric intake, individuals with these conditions may present deficiencies in essential micronutrients, such as magnesium, zinc, and selenium, which play key roles in metabolic, inflammatory, and antioxidant processes. This study aimed to evaluate micronutrient supplementation practices in patients with obesity and/or metabolic syndrome through the analysis of dietary intake and professional practices. In addition, it discusses the influence of nutritional ecology and the mismatch between modern diets and ancestral human physiology in the rising prevalence of nutritional deficiencies. Among the main methodologies employed, 18 adult patients diagnosed with obesity and/or metabolic syndrome answered the Food Frequency Questionnaire (ELSA-Brazil – reduced version) and another instrument assessing health status. For 17 health professionals (physicians and nutritionists), a structured questionnaire was applied to map clinical practices related to micronutrient screening and supplementation. The main findings revealed dietary intakes below the recommendations for all micronutrients assessed. Principal Component Analysis (PCA) and heatmap visualization indicated heterogeneous dietary patterns among participants. Regarding professional practice, there was wide variability in prescription strategies, administration routes, and criteria for evaluating treatment response, with no standardized protocols in place. Taken together, these findings suggest a high risk of subclinical deficiencies and highlight the need for personalized and standardized nutritional strategies, as well as training of health professionals for the appropriate management of these patients.
Keywords: Obesidade; Síndrome metabólica; Diabetes tipo 2; Suplementação; Micronutrientes; Magnésio; Zinco; Selênio; Obesity; Metabolic syndrome; Type 2 diabetes; Supplementation; Micronutrients; Magnesium; Zinc; Selenium; ACCNPQ::Ciências da Saúde::Nutrição